Image, Space, and the Contemporary Filmic Experience (Cinéma & Cie. Film and Media Studies Journal, 2012)
This article tackles the current debate dealing with the possibilities of expansion of contemporary cinema, trying to provide theoretical tools in order to build a framework, which takes into account the delicate relationship between space, image, and cinematic experience. Based on the background of researches devoted to cinema’s medium-specifity, the author identifies some possible contribution from Cultural, Media and Visual Studies, with the aim of formalizing some key-concept for the study of contemporary “cinematic forms”.